Tracking Neutrophil Intraluminal Crawling, Transendothelial Migration and Chemotaxis in Tissue by Intravital Video Microscopy - Xu, Najia (MyJove Corporation, 2011)
The recruitment of circulating leukocytes from blood stream to the inflamed tissue is a crucial and complex process of inflammation(1,2). In the postcapillary venules of inflamed tissue, leukocytes initially tether and roll on the luminal surface of venular wall. Rolling leukocytes arrest on endothelium and undergo firm adhesion in response to chemokine or other chemoattractants on the venular surface. Many adherent leukocytes relocate from the initial site of adhesion to the junctional extravasation site in endothelium, a process termed intraluminal crawling(3). Following crawling, leukocytes move across endothelium (transmigration) and migrate in extravascular tissue toward the source of chemoattractant (chemotaxis)(4). Intravital microscopy is a powerful tool for visualizing leukocyte-endothelial cell interactions in vivo and revealing cellular and molecular mechanisms of leukocyte recruitment(2,5). In this report, we provide a comprehensive description of using brightfield intravital microscopy to visualize and determine the detailed processes of neutrophil recruitment in mouse cremaster muscle in response to the gradient of a neutrophil chemoattractant. To induce neutrophil recruitment, a small piece of agarose gel (~1-mm(3) size) containing neutrophil chemoattractant MIP-2 (CXCL2, a CXC chemokine) or WKYMVm (Trp-Lys-Tyr-Val-D-Met, a synthetic analog of bacterial peptide) is placed on the muscle tissue adjacent to the observed postcapillary venule. With time-lapsed video photography and computer software ImageJ, neutrophil intraluminal crawling on endothelium, neutrophil transendothelial migration and the migration and chemotaxis in tissue are visualized and tracked. This protocol allows reliable and quantitative analysis of many neutrophil recruitment parameters such as intraluminal crawling velocity, transmigration time, detachment time, migration velocity, chemotaxis velocity and chemotaxis index in tissue. We demonstrate that using this protocol, these neutrophil recruitment parameters can be stably determined and the single cell locomotion conveniently tracked in vivo.